Intracranial neuroendocrine carcinoma with coexisting pituitary adenoma: a case report and comprehensive literature review - Kang, Wei; Feng, Miaomiao; Liu, Xintong; Duan, Anle; Tang, Beiyan; Yan, Hong; Dong, Qiang; Zhao, Xianjun; Duan, Lei; Pan, Yawen (Frontiers in Oncology, 2025)
Neuroendocrine carcinomas (NECs) originating from intracranial sites are exceedingly rare. Here, we present the case of a 29-year-old female with intracranial NEC coexisting with a pituitary adenoma (PA). The patient’s symptoms included intermittent headaches, visual impairment, and endocrine abnormalities. Imaging studies revealed a large lobulated mass in the left frontal lobe and a mass lesion in the sellar region. Laboratory investigations indicated elevated levels of prolactin (PRL) and growth hormone (GH). Surgical resection of the frontal lobe tumor was performed initially, followed by neuroendoscopic transsphenoidal resection of the sellar lesion. The case underscores the diagnostic complexity of intracranial NEC due to its nonspecific clinical and radiological manifestations. Surgery remains the primary treatment modality, with adjunctive radiotherapy and chemotherapy. Further research is essential to enhance diagnostic accuracy and refine treatment strategies for intracranial NEC.